Organizational and legal forms and goals of young scientists' communities: world experience - Moldashev, K.; Malgeldinov, N. (BUKETOV BUSINESS REVIEW, 2024)
Object: The research is aimed at analyzing the tasks and organizational and legal forms of communities of young scientists in various countries in order to understand their integration into decision-making mechanisms and the degree of their independence in formulating and communicating the interests of their members. Methods: The study includes a comparative analysis of five communities of young scientists from different geographical regions — Canada, Australia, Malaysia, Russia and Poland. When choosing communities, their active role in national academies and universities was taken into account. The data for the analysis were collected from the official online resources of the communities, with an emphasis on identifying key aspects of their activities and organizational structures. Findings: Young scientists play a key role in scientific progress and social development around the world. The communities of young scientists from different countries provide significant support to young scientists. These organizations have unique goals and methods, but they share a common goal — to promote scientific progress and sustainable development in their countries. Conclusions: Various organizational and legal forms of communities of young scientists — from national representative offices and networks to colleges and councils — serve a single purpose: to create conditions for career growth and development of young scientists. The approach of each country reflects its national characteristics, history and culture, which influence the formation of these communities.